2000
DOI: 10.1063/1.126406
|View full text |Cite
|
Sign up to set email alerts
|

Ion-beam-induced spinel-to-rocksalt structural phase transformation in MgAl2O4

Abstract: An ion-beam-induced metastable phase in magnesium aluminate spinel (MgAl2O4) has been examined in detail using transmission electron microscopy. Single crystals of MgAl2O4 with (111) orientation were irradiated with 180-keV Ne+ ions at 120 K to fluences of 1016 and 1017/cm2. Selected-area electron diffraction patterns obtained from the irradiation-induced damaged layer revealed that all even hkl reflections (e.g., 222) possess strong intensity, while all odd hkl reflections (e.g., 111) are weak. The features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 9 publications
7
36
0
Order By: Relevance
“…1, we have reported the diffraction diagrams of MgAl 2 O 4 prior and after irradiation. The same modifications as noted by Sickafus et al 4,5 are observed. These include the disappearance of all the (h k l) apart from the (4h, 4k, 4l) lines and partial amorphisation for the highest fluences.…”
Section: Results and Interpretationsupporting
confidence: 81%
See 1 more Smart Citation
“…1, we have reported the diffraction diagrams of MgAl 2 O 4 prior and after irradiation. The same modifications as noted by Sickafus et al 4,5 are observed. These include the disappearance of all the (h k l) apart from the (4h, 4k, 4l) lines and partial amorphisation for the highest fluences.…”
Section: Results and Interpretationsupporting
confidence: 81%
“…Prior to this amorphisation, drastic structural modifications have been observed and some authors have interpreted them as a crystalline phase transformation. 4,5 On the other hand, there is no clear evidence for the formation of extended defects such as dislocations loops or networks. 6 Such an inert matrix will be submitted to irradiation of different origins, namely fast neutrons, ␣ particles (∼6 MeV) and recoil atoms (∼240 amu, 100 keV) from natural actinides ␣-decay, fission products (∼80-150 amu, ∼70-100 MeV).…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, the work by Sickafus 8 on the structural analysis of MgAl 2 O 4 up on irradiation says that the lattice parameter changes from a = 0.808 nm (for unirradiated) to a = 0.404 nm (for irradiated) along with a change in space group from Fd3m to Fm3m. Moreover, an earlier report by Sickafus et al 9 clearly mentioned that the X-ray diffraction pattern of an ordered MgAl 2 O 4 should show higher intensity for all odd reflections like (3 1 1), etc., and it will be lower for all even reflections e.g. (2 2 2).…”
Section: Phase Analysismentioning
confidence: 94%
“…However, if the samples contain both ordered and disordered spinel (rocksalt structure), the intensity of all even reflections (2 2 2) will increase because (1 1 1) reflections for disordered spinel also occur at the same 2θ thereby increasing the intensity of (2 2 2). Sickafus et al 9 suggests that disordering takes place through a displacive transformation in which the atoms move to forbidden (interstitial) sites.…”
Section: Phase Analysismentioning
confidence: 99%
“…The motivation for this is due, at least in part, to the need to derive new materials with enhanced radiation resistance. Experimental work on spinel, carried out over a number of years, has shown that under neutron bombardment, a large number of cation anti-site defects 4 are produced and that in addition stable point defects, preceding either amorphisation or a transformation to a rocksalt structure, could be formed under high dose inert gas ion bombardment [5][6][7] . Classical molecular dynamics simulations that examined the ballistic phase of the cascade 1,2 also concluded that the predominant defects remaining after this phase were cation anti-site defects but that split Mg and O interstitial defects could occur orientated in <110> directions.…”
Section: Introductionmentioning
confidence: 99%